Confucius the man and the way of Gongfu - Ni, Peimin (Lanham Rowman & Littlefield, 2016)
Through a systematic introduction of Confucius as a historical figure, a spiritual leader, a philosopher, a political reformer, an educator, and a person (with a chapter for each of the above), this book offers a comprehensive, lucid, and yet in-depth articulation of Confucius and his teachings for modern Western students. It explains how his ideas are different from their Western counter parts as well as the dogmatized or overly intellectualistic understandings of Confucianism framed under the Western influence. The book reveals clearly how the Masters insights can be a rich resource for addressing contemporary problems and re-enchanting the world and the contemporary life.
Confucius as a historical figure -- Confucius as a spiritual leader -- Confucius as a philosopher -- Confucius as a political reformer -- Cofucius as an educator -- Confucius as a person.
Includes bibliographical references and indexes.
Keywords: Confucius; Confucius and Confucianism